The relationship between nurse staffing and inpatient complications - Schreuders, L.; Bremner, A.; Geelhoed, E.; Finn, Judith (WILEY-BLACKWELL, 2015)
Aim: To compare characteristics of hospitalizations with and without complications and examine the impact of nurse staffing on inpatient complications across different unit types. Background: Studies investigating the relationship between nurse staffing and inpatient complications have not shown consistent results. Methodological limitations have been cited as the basis for this lack of uniformity. Our study was designed to address some of these limitations. Design: Retrospective longitudinal hospitalization-level study. Method: Adult hospitalizations to high intensity, general medical and general surgical units at three metropolitan tertiary hospitals were included. Data were sourced from Western Australian Department of Health administrative data collections from 2004–2008. We estimated the impact of nurse staffing on inpatient complications adjusted for patient and hospital characteristics and accounted for patients with multiple hospitalizations. Results: The study included 256,984 hospitalizations across 58 inpatient units. Hospitalizations with complications had significantly different demographic characteristics compared with those without. The direction of the association between nurse staffing and inpatient complications was not consistent for different inpatient complications, nurse skill mix groups or for hospitalizations with different unit movement patterns. Conclusion: Our study design addressed limitations noted in the field, but our results did not support the widely held assumption that improved nurse staffing levels are associated with decreased patient complication rates. Despite a strong international focus on improving nurse staffing to reduce inpatient complications, our results suggest that adding more nurses is not a panacea for reducing inpatient complications to zero.